PERANCANGAN APLIKASI PENGENALAN ADAT KARO MENGGUNAKAN METODE AUGMENTED REALITY 3 DIMENSI - Teofilus Sitepu, Ray; Eko Suharyanto, Cosmas (LPPM Universitas Putera Batam, 2023)
North Sumatra is a province on the island of Sumatra which has several districts with various ethnicities, the Toba Batak, Mandailing, Pesisir, Nias, Simalungun, Fak-fak/Dairi, Malay, and Karo Batak. At present there are quite a number of Tanah Karo people who have chosen to move to other areas, live their lives in other areas because the condition of the mountains in Tanah Karo is getting older so that it becomes a concern for people who live close to the mountains and some of their descendants. Those who were born outside the Karo Land are somewhat forgotten about the traditional houses, musical instruments, clothing, regional dances originating from the Karo Land. Augmented Reality is part of the Virtual Environment technology or more commonly referred to as Virtual Reality (VR). Android is a Linux-based operating system for mobile phones that provides an open platform for developers to create their own applications so that they can be used by a variety of mobile devices. With the introduction of the Karo Indigenous application, it is hoped that it will be able to help in learning about the preservation of Karo Indigenous culture.